Effects of variety, altitude, and undersowing with legumes on the nutritive value of wheat straw - Schulthess, Urs C.; Tedla, A.; Mohamed-Saleem, M.A.; Said, A.N. (Cambridge University Press, 1995)
Wheat was planted at different altitudes in the Ethiopian highlands. Increased altitude led to a lower neutral detergent fibre (NDF) content and a higher in vitro organic matter digestibility (IVOMD) of the leaf blades, leaf sheaths and stems. The varieties tested did not differ in NDF content, However, because of the improved NDF digestibility of all three straw fractions. The semi-Dwarf varieties had a higher IVOMD than the standard tall wheats. The local durum wheat variety showed a much higher sodium content and a more favourable Na:K ratio. Undersowing with an equal mixture of Trifolium Ruepellianum (Fres.) and Trifolium steudneri (Schwf.) led to a small reduction in straw yield but increased the crude protein content of the crop residues from 2.3 to 7.1 percent and the IVOMD from 44 to 51 percent as compared to the sole wheat stand.